PEMENUHAN NAFKAH ANAK PASCA PERCERAIAN PERSPEKTIF HUKUM ISLAM - Hidayat, Samsul; Rahmania Kusumawati, Ita (USRATUNA: Jurnal Hukum Keluarga Islam, 2023)
Various legal consequences of Sharia law seem to not be implemented by the actors of divorce, especially child support. This ultimately has a negative impact on children as victims of their parents' separation. This research aims to determine how divorced parents fulfill child support obligations for children who are currently studying at three pesantrens (Islamic boarding schools) in the Nganjuk area. The three pesantrens are: Pondok Pesantren Miftahul Mubtadi'in Ar-Ridlo in Tanjunganom Village, Tanjunganom District, Nganjuk Regency; Pondok Modern Darul Ihsan in Payaman Village, Nganjuk District, Nganjuk Regency; and Pondok Pesantren Gedongsari in Tegaron Village, Prambon District, Nganjuk Regency. This research is a descriptive field research using a phenomenological approach. Primary data sources were obtained through interviews and documentation of the actors of broken homes, children as victims, and the pesantren ustadz as their caregivers, supported by secondary data in the form of literature or scientific works. The results of this study found that almost all fathers (former husbands), who are obligated to provide child support, do not provide it. The party that ends up providing child support after divorce is the mother.